trig. please help

Asked by  | 5th Aug, 2008, 03:44: PM

Expert Answer:

Cos  θ  +  Sin θ = 2 cos θ

      2 cosθ -- cosθ  ==sinθ

  cos θ (  2 --1)  =sinθ

therefore   cos θ    --- sin θ  =  cosθ  -- cosθ( 2  --1)  =cos θ --2 cosθ + cosθ

                                                                                             =2cosθ --2 cosθ

                                                                                             = cosθ (2 -- 2)

Answered by  | 5th Aug, 2008, 05:12: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.